Road transport and economic development - Singh, Ratan Kumar (New Delhi : Deep & Deep, 1988)
Study of Bihar.
Includes index.
Bibliography: p. [260]-265.
Keywords: Roads -- India -- Bihar; Bihar (India) -- Economic conditions